Zonificación de sectores estratégicos para el abastecimiento de agua en el municipio de Madrid, Cundinamarca - Lizarazo López, Xiomara Andrea (Universidad Antonio Nariño, 2022)
This document proposes a model that allows identifying those sectors that, due to their biophysical characteristics, are strategic for the water supply in the municipality of Madrid, Cundinamarca, through the application of GIS tools. For the development of the model, it was necessary to collect historical data from the meteorological stations present in the study area, as well as the inputs available in the SIAC (Environmental Information System of Colombia), Geoportal IGAC (Agustin Codazzi Geographical Institute) and Earthdata (SRTM mission) to obtain the Digital Elevation Model (DEM).